A survey of a mixed species aviary provides new insights into the pathogenicity, diversity, evolution, host range, and distribution of psittacine and passerine adenoviruses. Issue 5 (3rd September 2019) - Phalen, David N.; Agius, Jessica; Vaz, Frederico F.; Eden, John-Sebastian; Setyo, Laura C.; Donahoe, Shannon
ABSTRACT: A Bourke's parrot ( Neopsephotus bourkii ) originating from an aviary in Australia, containing two species of parrots, five species of finch and a species of dove, was presented for necropsy. The Bourke's parrot died from gastritis caused by Macrorhabdus ornithogaster, but also had an interstitial nephritis and ureteritis with adenovirus-like inclusion bodies within collecting duct epithelial cells. The adenovirus causing the lesions was shown to be Psittacine adenovirus-2 (PsAdV-2) using a PCR assay specific for adenoviruses and sequencing of amplicons. A survey of droppings from other birds in the aviary using the same PCR assay with amplicon sequencing found a high prevalence of infection of PsAdV-2 in Bourke's and scarlet-chested parrots ( Neophema splendida ). PsAdV-2 was also present in droppings from a Namaqua dove ( Oena capensis ). Gouldian finches ( Erythrura gouldiae ), red-billed firefinches ( Lagonosticta senegala ), and red-throated parrot finches ( Erythrura psittacea ) were shedding Gouldian finch adenovirus-1 (GFAdV-1). Two novel adenoviruses, an atadenovirus and a siadenovirus, were detected in the droppings from long-tailed finches ( Poephila acuticauda ). Kidney tissue from three of four scarlet-chested parrots submitted for necropsy from a second aviary were also positive for PsAdv-2. These findings and previously reported findings of widespread PsAdv-2 infection in captive orange-bellied parrots ( Neophemia chrysogaster ) raise the possibility that PsAdV-2 is enzootic in Australian aviculture. This represents the first report of GFAdV-1 in Australia and first identification of infection in finch species other than the Gouldian finch. Identification of two novel adenoviruses in long-tailed finches suggests that other novel adenoviruses are circulating in other finch species. RESEARCH HIGHLIGHTS Psittacine adenovirus-2 was present in high prevalence in two Australian aviaries. Gouldian finch adenovirus-1 (GFAdV-1) was detected in Australia for the first time. The host range of GFAdV-1 host range was expanded to other finch species. Novel atadenovirus and siadenovirus were detected in Estrildid finches.